Complex antioxidants in a randomized single-blinded study of memory in seniors. - Summers, William K.; Martin, Roy L.; Liu, Yimeng; Peña, Bernice; Marsh, Gary M. (Aging Clinical & Experimental Research, 2018)
Introduction: Oxidative injury to the brain and aging are theoretical co-causes of Alzheimer’s Disease (AD). Amyloid plaques and tangles are then secondary phenomenon. The preclinical state would then be ‘normal’ elderly.Methods: A potent complex antioxidant (antiOx) was tested against a popular one-a-day multivitamin (mV) in a randomized single blind design in ‘normal’ senior subjects over 6 months. Memory testing was done at baseline, 1, 3, and 6 months. The generalized estimating equation (GEE) approach was used to compare the change score of NLT100 and 20WR between two groups over time.Results: Analysis of the antiOx group (30 subjects) demonstrated significant improvement in declarative memory (change score for NLT100 at month 6 = 6.36 p < 0.0001) and working memory (change score for 20WR at month 6 = 3.23, p < 0.0001). A change-score analysis over 6 months suggests possible neurogenesis in the antiOx group. The mV group (33 subjects) had a change score of the NLT100 and 20WR on the sixth month of 2.20 and 0.32 (p = 0.07, 0.35).Conclusions: A complex antioxidant blend, sold as an over-the-counter (OTC) supplement, can improve memory in elder subjects. Antioxidants may be beneficial in AD and other neurodegerative diseases.